P-220-Escherichia coli displaying virulence features of multiple diarrheogenic pathotypes detected in a Crohn's disease patient - Santos, Ana Carolina da Silva [UNESP]; Rodrigues, Josias [UNESP]; Romeiro, Fernando Gomes [UNESP]; Sassaki, Ligia Yukie [UNESP] (Oxford University Press (OUP), 2014)
Background: The number of Escherichia coli in the gut of Crohn's disease (CD) patients is higher than that of normal subjects, but the virulence potential of these bacteria is not fully known. Previous studies have shown that these E. coli are closely related to extraintestinal pathogenic categories (ExPEC), are able to invade epithelial cells, and usually do not produce exotoxins. We report here the detection, in a CD patient, of an E. coli which belongs to a classical enteropathogenic (EPEC) serotype and displays virulence markers of enteroinvasive (EIEC), enteroaggregative (EAEC) and enterohemorrhagic (EHEC) pathotypes. Methods: The E. coli strain was isolated, in 2009, by classical bacteriological procedures from a 56 year old woman who underwent ileo-terminal resection 1 year before, due to intestinal obstruction. The bacterial characterization was carried out by in vitro adhesion and invasion assays to cultured epithelial cells and macrophages and screening by PCR to identify virulence genetic markers of diarrheogenic E. coli (DEC) and to detect one of the gene combinations which define the phylogroups of the E. coli reference (EcoR) collection. The strain was also tested for the ability to produce biofilm and shiga cytotoxins and had its whole genome sequenced by Ion Torrent Sequencing Technology. Results: The studied strain, which was detected both in ileum biopsies and the stools of the patient, displayed the aggregative adherence (AA) phenotype to Hep-2 cells and an ability to enter Caco-2 cells 3x as high as that of EIEC reference strain and 89% of that of the prototype AIEC LF82 strain. Although it could invade cultured macrophages, the strain was unable to replicate inside these cells. PCR screening revealed the presence of eae, aggR and stx1. Tests with bacterial culture supernatants in Vero cells demonstrating cytotoxicity suggested the production of Stx1. In addition, the strain revealed to be a strong biofilm producer, belonged to the B2 EcoR phylogroup, to the O126:H27 serogroup and to the multilocus sequencing type (MLST) ST3057. The 2 later features were deduced from the whole genome sequence of the strain. Conclusions: The characterization of this E. coli isolate from a CD patient revealed a combination of virulence markers of distinct DEC pathotypes, namely eae and stx1 of EHEC, AA, aggR and biofilm formation of EAEC, and invasiveness of EIEC. These features along with its serotype and phylogroup identity seem to suggest a potential to be involved in CD, an observation which should be tested with additional studies.